Playing with PtII and ZnII Coordination to Obtain Luminescent Metallomesogens. Issue 21 (20th March 2020) - Andelescu, Adelina‐Antonia; Heinrich, Benoît; Spirache, Maria Angela; Voirin, Emilie; La Deda, Massimo; Di Maio, Giuseppe; Szerb, Elisabeta I.; Donnio, Bertrand; Costisor, Otilia
Abstract: Blue–green luminescent terpyridine‐containing Pt II and Zn II complexes are reported. Equipped with lipophilic gallate units, which act as monodentate ancillary coordinating ligands and/or as anions, they display low‐temperature mesomorphic properties (lamello‐columnar and hexagonal mesophases for Pt II and Zn II complexes, respectively). The mesomorphic properties were investigated by polarised optical microscopy, differential scanning calorimetry, thermogravimetric analysis and X‐ray scattering of bulk materials and oriented thin films. The model of self‐assembly into the lamello‐columnar phase of the Pt II complex has been described in detail. The optical properties of the complexes were investigated in the liquid and condensed liquid crystalline states, highlighting the delicate balance between the role of the metal in determining the type of excited state responsible for the emission, and the role of the ancillary ligand in driving intermolecular interactions for proper mesophase formation. Abstract : Low‐temperature mesomorphism was obtained for Pt II and Zn II coordination complexes by playing with the coordination ability of a lipophilic gallate unit. The delicate balance between induction of mesomorphism and luminescence in condensed states is discussed (see figure).